Experimental Models of Infectious Pulmonary Complications Following Hematopoietic Cell Transplantation - Zhou, Xiaofeng; Moore, Bethany B. (Frontiers in Immunology, 2021)
Pulmonary infections remain a major cause of morbidity and mortality in hematopoietic cell transplantation (HCT) recipients. The prevalence and type of infection changes over time and is influenced by the course of immune reconstitution post-transplant. The interaction between pathogens and host immune responses is complex in HCT settings, since the conditioning regimens create periods of neutropenia and immunosuppressive drugs are often needed to prevent graft rejection and limit graft-versus-host disease (GVHD). Experimental murine models of transplantation are valuable tools for dissecting the procedure-related alterations to innate and adaptive immunity. Here we review mouse models of post-HCT infectious pulmonary complications, primarily focused on three groups of pathogens that frequently infect HCT recipients: bacteria (often P. aeruginosa), fungus (primarily Aspergillus fumigatus), and viruses (primarily herpesviruses). These mouse models have advanced our knowledge regarding how the conditioning and HCT process negatively impacts innate immunity and have provided new potential strategies of managing the infections. Studies using mouse models have also validated clinical observations suggesting that prior or occult infections are a potential etiology of noninfectious pulmonary complications post-HCT as well.